PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN GARAM BERYODIUM “KAPAL TERBANG” DI PASAR JONGGOL, KABUPATEN BOGOR - Fadli Za’far Sodik; Nuridin (Jurnal Ekonomi dan Industri, 2021)
The purpose of this study was to determine the effect of product quality and price on purchasing decisions of iodized salt "Kapal Terbang" in Jonggol Market, Bogor Regency ". This research is included in the category of causal associative research using a quantitative approach. In this study, the population used was 150 UD consumers. Sinar Laut, with the iodized salt brand "Kapal Terbang", is located in Jonggol Market, Bogor Regency. The technique used for sampling data is a random system (random sampling). This study took a sample with the Slovin method and obtained a sample of 60 respondents. The data analysis technique used in this research is to use multiple linear regression analysis. Based on the description that has been stated above. So it can be concluded that: simultaneously it shows that the variable product quality and price have a significant effect on the purchasing decision variable of iodized salt "Kapal Terbang" in Jonggol Market, Bogor Regency.